Islam in Transcultural and Postcolonial Realities: Questioning Traditionalism and Westernization in Leila Aboulela’s Bird Summons: Islam dalam Realitas Transkultural dan Pascakolonial: Mempertanyakan Tradisionalisme dan Baratisasidalam “Bird Summons” karya Leila Aboulela - Hamdoune, Yassine (Journal of Literature and Education, 2025)
Leila Aboulela’s novel Bird Summons (2019) dramatizes the effects of cultural encounters in reconsidering the deeply rooted principles of traditionalism and negotiating the modern Western tenets. It reveals numerous aspects of ambivalence, complexity, and potentiality, asserting the inevitability of change under the conditions of transculturality and postcoloniality. The article pinpoints the intrinsic motifs behind negating traditionalism while ‘Islamizing’ the Western tenets by three Muslim women, living in Scotland. It follows a qualitative methodology with a close reading of the Bird Summons. The theoretical framework consists of Mohammed Arkoun’s rereading Islam to overcome the dogmatic attitude of the traditional schools of thought, and Bill Ashcroft’s concept of ‘the translation’ and ‘postcolonial utopianism’ to evince the entanglements that cover postcolonial subjectivity, and to identify the role of freedom in constructing postcolonial subjectivity. The article concludes that traditionalism distorts the Islamic discourse, which requires reshuffling the cultural strata upon which the traditional Islam is established while demonstrating how transcultural and postcolonial realities accelerate the Traditional Islamic paradigm shifting.